Enhanced Weathering Triggered the Transient Oxygenation Event at ∼1.57 Ga. Issue 15 (9th August 2022) - Tang, Dongjie; Fu, Xuewu; Shi, Xiaoying; Zhou, Limin; Zheng, Wang; Li, Chao; Xu, Dongtao; Zhou, Xiqiang; Xie, Baozeng; Zhu, Xiyan; Jiang, Ganqing
Abstract: The mid‐Proterozoic (∼1.8–0.8 Ga) is characterized by low atmospheric oxygen and pervasive oceanic anoxia, with transient oxygenation events. One of the oxygenation events happened at ∼1.57 Ga, during which atmospheric O2 may have reached ≥4% present atmospheric level (PAL) and thus promoted the evolution of multi‐cellular eukaryotes. The cause of this oxygenation event, however, remained unknown. Here, we report δ 202 Hg, ∆ 199 Hg, P concentration, Rb/Al, and εNd (t) data across the ∼1.57 Ga oxygenation event in the Gaoyuzhuang Formation of North China. The positive δ 202 Hg, εNd (t), and negative Δ 199 Hg shifts, plus the accompanied peaks in Rb/Al, P, and I/(Ca + Mg), suggest that this oxygenation event was likely resulted from enhanced weathering of intermediate to mafic rocks, which may have promoted primary production via increasing P influx to the ocean and led to the rise in oxygen levels. The data indicate that enhanced weathering input could trigger transient oxygenation events during the mid‐Proterozoic. Plain Language Summary: During the mid‐Proterozoic (∼1.8–0.8 Ga), the oxygen concentrations in atmosphere and shallow oceans were persistently low but occasionally interrupted by transient oxygenation events. The origin of these short‐lived oxygenation events, however, is not properly understood. To reveal the potential causes behind these oxygenation events, we take the ∼1.57 Ga oxygenation event as an example to perform mercury (Hg) isotope, εNd (t), major and trace element analyses. The results show that this oxygenation event is associated with high δ 202 Hg, εNd (t), Rb/Al and low Δ 199 Hg values, as well as an increase in phosphorus concentration. The most plausible explanation for these data is that enhanced weathering of intermediate to mafic rocks led to an increase of nutrient input (e.g., phosphorus) to the ocean, resulted in high ocean primary productivity and oxygen release, and triggered the transient oxygenation event. Key Points: Hg‐enrichment recognized in the middle Gaoyuzhuang Formation, North China, coincides with the transient oxygenation event at ∼1.57 Ga Positive δ 202 Hg, Rb/Al and negative Δ 199 Hg shifts suggest that the Hg enrichment was resulted from enhanced terrestrial weathering Enhanced weathering increased phosphorous input and primary production in the ocean and triggered the oxygenation event at ∼1.57 Ga